Pola Komunikasi Organisasi Dalam Mendukung Pelayanan Publik Di Dinas Kependudukan Dan Pencatatan Sipil Kota Surakarta - Sheila, Aldhea; Nurnawati; Siswanto, Siswanto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This research aims to examine the organizational communication patterns implementedat the Department of Population and Civil Registration (Disdukcapil) of Surakarta City insupporting public service delivery. Effective organizational communication is essential inpublic service institutions to ensure that services are delivered responsively, accurately, andefficiently. This study employs a qualitative research method, with data collection techniquesincluding observation, interviews, and documentation. Data validity was tested usingtriangulation of methods and sources. The research findings indicate that DisdukcapilSurakarta applies a circular communication pattern to support public services. In this model,each team member is given an equal opportunity to express opinions and offer solutions toexisting problems, fostering a collaborative and participatory work environment. In addition,Disdukcapil employs other communication patterns, such as primary communication throughdirect interaction during internal meetings, secondary communication via social media andinformation systems, and linear communication through one-way dissemination ofinformation without feedback. However, the circular pattern is the most dominant, enablingtwo-way communication that involves feedback both among staff during coordination meetingsand between service officers and the public during consultations. This approach ensuresflexibility and responsiveness in problem-solving, improves internal collaboration, enhancesthe quality and effectiveness of public services, and ultimately increases public satisfaction withthe services provided by Disdukcapil Surakarta.